Management Intensity Controls Nitrogen-Use-Efficiency and Flows in Grasslands—A 15N Tracing Experiment - Marcus Zistl-Schlingmann; Steve Kwatcho Kengdo; Ralf Kiese; Michael Dannenmann (Agronomy, 2020)
The consequences of land use intensification and climate warming on productivity, fates of fertilizer nitrogen (N) and the overall soil N balance of montane grasslands remain poorly understood. Here, we report findings of a 15N slurry-tracing experiment on large grassland plant–soil lysimeters exposed to different management intensities (extensive vs. intensive) and climates (control; translocation: +2 °C, reduced precipitation). Surface-applied cattle slurry was enriched with both 15NH4+ and 15N-urea in order to trace its fate in the plant–soil system. Recovery of 15N tracer in plants was low (7–17%), while it was considerably higher in the soil N pool (32–42%), indicating N stabilization in soil organic nitrogen (SON). Total 15N recovery was only 49% ± 7% indicating substantial fertilizer N losses to the environment. With harvest N exports exceeding N fertilization rates, the N balance was negative for all climate and management treatments. Intensive management had an increased deficit relative to extensive management. In contrast, simulated climate change had no significant effects on the grassland N balance. These results suggest a risk of soil N mining in montane grasslands under land use intensification based on broadcast liquid slurry application.